2016
DOI: 10.1128/jcm.02460-15
|View full text |Cite
|
Sign up to set email alerts
|

The “3 in 1” Study: Pooling Self-Taken Pharyngeal, Urethral, and Rectal Samples into a Single Sample for Analysis for Detection of Neisseria gonorrhoeae and Chlamydia trachomatis in Men Who Have Sex with Men

Abstract: c Triple-site testing (using pharyngeal, rectal, and urethral/first-void urine samples) for Neisseria gonorrhoeae and Chlamydia trachomatis using nucleic acid amplification tests detects greater numbers of infections among men who have sex with men (MSM). However, triple-site testing represents a cost pressure for services. MSM over 18 years of age were eligible if they requested testing for sexually transmitted infections (STIs), reported recent sexual contact with either C. trachomatis or N. gonorrhoeae, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 25 publications
(30 reference statements)
4
74
2
1
Order By: Relevance
“…Pooling of urine specimens from multiple individuals has been shown to be sensitive and specific for CT testing15 16 and the effectiveness of pooling specimens from different anatomical sites within an individual for CT and NG detection has been demonstrated previously 11. These workers tested throat and rectal swabs and urine samples in MSM using the AC2 assay and demonstrated high negative predictive values for pooled sample testing.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Pooling of urine specimens from multiple individuals has been shown to be sensitive and specific for CT testing15 16 and the effectiveness of pooling specimens from different anatomical sites within an individual for CT and NG detection has been demonstrated previously 11. These workers tested throat and rectal swabs and urine samples in MSM using the AC2 assay and demonstrated high negative predictive values for pooled sample testing.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that the dilutional effect of the urine in the pooled specimens was responsible for the apparent reduced sensitivity for the solitary rectal CT infections. Sultan et al 11 also found single site infections accounted for almost all of their missed CT and NG infections with pooled specimen testing, but found the throat swabs were less sensitive than the rectal swabs. Direct comparison of pooled testing and individual specimen testing using the GeneXpert would help address this.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…National data from the Netherlands suggests that a majority of chlamydial and gonococcal infections in MSM would be missed if extragenital sites are not tested (77), although there is no published cost effectiveness data to compare this strategy with history-directed testing. Pooling of samples from pharynx, urine and rectum may be a means of reducing costs (78). It is desirable that hepatitis B vaccination is offered in all settings but the advantages of expanding the availability of HIV and STI testing should not be lost if this is not practicable in outreach situations.…”
Section: The Range Of Tests Providedmentioning
confidence: 99%
“…Extra genital screening tests patients in their genital, urethral, and pharyngeal sites. Although urine is most widely used to test for CT/GC infection, it is still recommended to test all three sites as an individual's sexual practices can place them at greater risk for infection, depending on the type of sex they are having (13,15) . Information on the underlying disparities regarding prevalence and incidence of disease is necessary for bridging the gap in services.…”
Section: Introductionmentioning
confidence: 99%